The Effect of Drilling Fluid on Coal's Gas-Water Two-Phase Seepage. (16th June 2022) - Zhang, Xianyong; Zheng, Shuangjin; Bai, Kai
Abstract : In the process of coal bed methane (CBM) production, the output of CBM is mainly related to the relative permeability of gas and water in coal seams. However, during the drilling process, the invasion of drilling fluid into CBM reservoirs changes the wettability, which may cause the gas and water's redistribution through the pores and cracks, further changing their two-phase seepage characteristics and influencing CBM production. Therefore, studying the effect of drilling fluid on coal's gas-water two-phase seepage has practical implications. Using a steady-state method, the influence of changing wettability and reducing the solution's interfacial tension on relative permeability is investigated by adding different surfactants. The increase in coal's hydrophilicity exhibits an impact on its relative gas-water permeability. At the same water saturation level, the relative gas permeability decreases and the relative water permeability increases. The hydrophilicity of coal was enhanced after adding anionic surfactants, which reduced gas permeability. Cationic surfactants are difficult to adsorb to the surface of coal due to the fact that the interfacial tension of the water and coal surface is reduced when the coal seam water is added to the cationic surfactants. After adding cationic surfactants, the gas permeability increased in favor of CBM production. The findings of this study could help to better understand the influence of drilling fluid intrusion on coal's gas-water two-phase seepage and provide technical guidance for selecting better surfactants during the preparation of drilling fluids and help to increase CBM production.